By the Spirit we understand: how do new religious experiences create scriptures? - Wreford, Mark Paul (2019)
This thesis is concerned with the relationship between religious experiences (REs) and the creation of the texts which became NT Scripture. It explores the possibility that certain REs were understood as revelatory and consequently inspired the writing of NT texts. Although the processes by which these texts were treated as scriptural by the earliest Christian community and came to be canonised are often subject to scholarly scrutiny, the connection is rarely made with the writers’ experiences of God. This means that the academic discourse rarely reaches to the question of the relationship between RE and notions of inspiration: what role did REs have in causing the writers to write? And what did they think they were doing when they were writing? This thesis addresses both questions. First, it reflects on the importance of the REs of a writer and their audience for the understanding of the writing itself. Because many NT texts make prominent claims about encounters with God, this is in some ways an obvious point. Nevertheless, the widespread presupposition of naturalist explanatory models means that this element is often missing in historical analyses of the NT. My first section (chs 2 and 3) will contribute to this discussion. Having first situated my study within a Forschungsgeschiche of research into RE (ch 2), I will outline a constructive theoretical approach to RE, including a heuristic definition of RE in the NT (ch 3). In the second section (chs 3-7), I will argue that experiences which fit within this definition are presented as key elements in shaping the NT texts by considering Luke-Acts and Galatians as indicative examples of a broader pattern. Thus, my thesis emphasises the simple but often forgotten truth that the NT texts claim to exist because of REs which inculcated a felt need for communication. Consequently, they cannot be properly understood without this element, even if other motivations may also have contributed to the decision to write. Second, this thesis reflects on the scriptural status of these texts. This question is usually asked only after the production and initial reception of the text in its immediate target audience, but as part of my analysis in the second section of the thesis (chs 3-7), I will argue that potential scripturality can be seen as a part of the initial production and reception process. The general assumption is that the authoritative status many NT texts appear to have had from a relatively early stage in their reception history and which ultimately manifested itself in their canonisation reflects later developments, rather than the intentions of their creators. My research focuses on the question of whether the NT writers did in fact intend to claim this kind of religious authority for their writings on the basis that they convey revelatory content derived from REs. I will consider Luke-Acts as a paradigmatic example of the relationship between RE and the creation of Scripture in chapters 4 and 5 because it offers an extensive narrative which reflects on early Christian claims to Spirit-inspired witness and begins with an explicit authorial statement of purpose. In chapter 4, I argue that Luke’s Pentecost narrative describes a RE in which human speech becomes theophanic. Combined with the sound of the wind and the appearance of fire, the tongues-speech at Pentecost makes the presence of God (the outpoured Spirit) noticeable, both to those filled and to the surprised crowd. In this way, it performs a revelatory function, and Peter’s sermon — an inspired reflection on Scripture which interprets the outpouring of the Spirit as a part of the story of God’s mighty deeds — is presented as functioning in a similar way. The fifth chapter unfolds how Luke describes the decision-making process which leads to the creation of the Apostolic Decree (Acts 10-15), which is presented as an authoritative writing within his own text. I focus on how he combines ecstatic visions and further tongues-speech with reflection to produce an authoritative document which makes an implicit claim to be inspired. Bringing this into conversation with Luke’s expressed purpose in the prologue (Luke 1:1-4), I argue that he intends to make a similar claim to authority and inspiration for his own writing: Luke-Acts offers a textual witness to Christ — the activity for which the Spirit is poured out — which is intended to be authoritative for its readers. On this basis, I argue that Luke intended to write a scriptural account of the acts of God discerned in the REs of his eyewitness sources. Chapter 6 focuses on Galatians in order to argue that Paul’s autobiographical account of God’s revelation of Christ to him is the foundation of a letter which is intended to fulfil a scriptural function for its addressees after the pattern identified in Luke-Acts. In this letter, Paul offers insight into his own initial encounter and ongoing relationship with Christ and uses this as a starting point in his attempt to offer an authoritative account of the gospel which should act as a norm for the recipients. Consequently, it is reasonable to suggest that Paul intended to write a text which had the same status as his spoken proclamation of the gospel because it acts as an adequate conduit for, and deposit of such a proclamation. Given that Paul conceived of his own embodied ministry partly in terms derived from the OT prophetic texts (Gal 1:15-16), I argue that the textualization of his gospel message in this letter implies that he intended to write a text that would function as Scripture for its addressees on the basis of its close connection to his own RE. In response to the questions this thesis is intended to address, I argue first that in Luke-Acts and Galatians REs are presented as the reason for the existence of the texts and that they appear to have shaped what is written. Second, I claim that both Luke and Paul understood themselves to be creating new scriptural writings on the basis of their relationship to new REs.